2014
DOI: 10.1093/nar/gku079
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of six somatic linker histone H1 variants in human breast cancer cells uncovers specific features of H1.2

Abstract: Seven linker histone H1 variants are present in human somatic cells with distinct prevalence across cell types. Despite being key structural components of chromatin, it is not known whether the different variants have specific roles in the regulation of nuclear processes or are differentially distributed throughout the genome. Using variant-specific antibodies to H1 and hemagglutinin (HA)-tagged recombinant H1 variants expressed in breast cancer cells, we have investigated the distribution of six H1 variants i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
129
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(147 citation statements)
references
References 107 publications
13
129
1
Order By: Relevance
“…Expression of H1.4-K26A induced both up-and down-regulation of gene expression compared with H1.4-WT expression, consistent with both active and repressive effects of H1.4-K26 PTMs. Very few genes presented altered expression in opposite senses whether H1.4 was overexpressed or knocked down, and we do not believe that this is due to specific binding of H1.4 to these promoters, as we have previously reported that all gene promoters are bound by any H1 variant quite indistinctly [42]. We have shown here that a subset of genes differentially expressed upon H1.4 overexpression do not contain significant enrichment of this variant.…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…Expression of H1.4-K26A induced both up-and down-regulation of gene expression compared with H1.4-WT expression, consistent with both active and repressive effects of H1.4-K26 PTMs. Very few genes presented altered expression in opposite senses whether H1.4 was overexpressed or knocked down, and we do not believe that this is due to specific binding of H1.4 to these promoters, as we have previously reported that all gene promoters are bound by any H1 variant quite indistinctly [42]. We have shown here that a subset of genes differentially expressed upon H1.4 overexpression do not contain significant enrichment of this variant.…”
Section: Discussionsupporting
confidence: 44%
“…4). Active genes (CDK2, JUN), but not repressed genes (NANOG), showed local H1.2 (WT or mutant) depletion at the transcription start sites (TSS) compared with the corresponding upstream promoter region, as described elsewhere [33,42].…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Knock-out of Hmgn1 and Hmgn2 in mouse embryo fibroblasts results in the loss of DNase I-hypersensitive sites, particularly at enhancer regions (63). In breast cancer cells, the depletion of certain H1 subtypes, including H1.2, is associated with histone marks indicative of strong enhancers (37). A recent publication has also shown that the pioneer factor forkhead box A (FOXA) displaces H1 at enhancers in mouse hepatocytes, and the displacement of H1 promotes accessibility of the underlying nucleosomes and binding of liver-specific transcription factors (64).…”
Section: Discussionmentioning
confidence: 99%
“…8E) or total H1 or H3 (data not shown) were observed. Moreover, these ChIP results confirmed that H1X was not the only H1 variant occupying these H1X-responsive promoters.We and others have reported elsewhere that there is a valley in H1 occupancy at active promoters compared with that in surrounding regions (40,41). We compared H1 occupancy at TSS and Ϫ3 kb upstream (the distal promoter).…”
mentioning
confidence: 99%